Innovation, Entrepreneurship and Clusters in Latin America Natural Resource: Implication and Future Challenges - Bas,Tomas Gabriel (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2008)
The natural resources play a very important role in the economy of the Latin America countries, but follow the classical models of resource exploitation and scale do not add much more value to the products or services like other knowledge-based industries (biotechnology or IT). The cluster approach assembled around the pattern of innovation and entrepreneurship characteristics can help to improve these kinds of industries. Nevertheless, the "Natural Resource Clusters" have a particular task and they are based primary in environmental characteristics. However, this type of clusters is very different from "Technology Clusters" with a high innovation and entrepreneurship structure that needs explicitly more intellectual capacities and non-specific environmental characteristics. The authors suggest that in Latin America, clusters, innovation and entrepreneurship based in the natural resources has a supplementary significance, but they need add much value based in the knowledge. This article discuss the challenge of Latin American economies and the implication to transform the natural resources based industries in others with more innovation and knowledge based assets and shows a framework based on Chile's particular experiences on salmon; wine and mining industries. Economics implications and future research are discussed.